2017
DOI: 10.1016/j.nedt.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Academic dishonesty among Italian nursing students: A longitudinal study

Abstract: Considering the ethical issues related to nursing and that Ethics is an integral part of the nursing education in the\ud degree course, one would suppose that academic dishonesty might be less frequent in nursing students than in\ud students of other disciplines. However, several studies show that this trend of deceitful behaviour seems to be\ud similar among the university nursing students and those of other disciplines.\ud The aim of this study is to investigate the phenomenon of academic dishonesty in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 35 publications
(49 reference statements)
1
37
0
2
Order By: Relevance
“…The consequence of these undesired behaviours violates trust in the nursing profession to appropriately value human life and care for patients with honesty. It was found that student nurses who were academically dishonest were more likely to commit dishonest acts in clinical practice and this can often translate into harmful patient outcomes [1,3,5,8].…”
Section: Implications Of Students' Engagement In Acts Of Academic Dismentioning
confidence: 99%
See 4 more Smart Citations
“…The consequence of these undesired behaviours violates trust in the nursing profession to appropriately value human life and care for patients with honesty. It was found that student nurses who were academically dishonest were more likely to commit dishonest acts in clinical practice and this can often translate into harmful patient outcomes [1,3,5,8].…”
Section: Implications Of Students' Engagement In Acts Of Academic Dismentioning
confidence: 99%
“…Academic dishonesty amongst nursing students has become a common occurrence and has drawn a great amount of public scrutiny in recent times [1][2][3]. This is often viewed as the starting point of legal agitation to nursing educators because of the possible impact this will have on existing and subsequent professional practice and patient care [4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations